The Implementation of Genre Based Approach and Using Read-Examine-Decide-Write Strategy (REDW) on Students’ Reading Comprehension of Report Text - Yuherna, Siti; Rosyid, Abdul (Journal of English Teaching and Linguistics Studies (JET Li), 2024)
Reading is a process that aims to find or dig information from a text. The problem faced by students is their weak ability to get information or extract information from a text. This is caused by the low vocabulary understood by students, causing students to have difficulty understanding reading texts, especially in finding main ideas and specific information. Therefore, an effort is needed to explore the potential possessed by each student. This effort can be done in various ways, such as applying the Genre Based Approach and using the REDW (Read-Examine-Decide-Write) strategy during the learning process in class in an effort to improve students' skills in understanding reading texts. This research was conducted on students of SMAN 6 Bogor class X IPS 2, totaling 33 students. In this study, the researcher used the Kemmis Mc.Taggart PTK method, which in its research flow included planning, implementation, observation, and reflection. The researcher gave pre-tests, treatments and post-tests to the research samples. Based on the results of research on the application of the Genre Based Approach and the REDW strategy in the English subject, Report Text material in class X IPS 2 can improve learning outcomes, especially in reading report text skills. In the pra-siklus activities of 21 students there was 1 (0.5%) student who achieved KKM with an average grade of 49, siklus I increased to 7 (33%) students with an average grade of 66 and in siklus II increased to 13 (65%) students who scored above the KKM with an average grade of 78.